Build Organizational Citizenship Behavior Toward Environment Through Organizational Culture, Organizational Commitment and Mediated Self-efficacy - Adu, Jekson; Nawangsari, Lenny C. (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
Purpose – This study aims to determine the direct positive and significant influence of Organizational Culture on OCBE, Organizational Commitment, and Self-efficacy and indirectly between Organizational Culture and Organizational Commitment to OCBE mediated by Self-efficacy on employees in a Metal Packaging Company. Methodology/approach – This study uses the SEM PLS analysis method where the data processing uses the SmartPLS 3.0 application. Based on the results of research through questionnaires to 129 employees. Findings – From this study, it was found that there was a positive and significant effect of the direct relationship between Organizational Culture and Self-Efficacy on OCBE, as well as Organizational Commitment to Self-Efficacy. There is a non-positive and insignificant effect of Organizational Commitment to OCBE. As for the indirect relationship, self-efficacy failed to mediate the relationship between organizational culture and OCBE but succeeded in mediating the relationship between Organizational Commitment and OCBE. Novelty/value – This research has contributed to the development of existing research construct models. The contribution of organizational culture variables and organizational commitment to self-efficacy is 0.502, organizational culture and organizational commitment to OCBE is 81.6% while the remaining 18.4% is influenced by other variables not examined in this study.